Penataan Karya Tari Kipas Chandani Sebagai Materi Tari Kreasi Baru Di Universitas PGRI Palembang - Rully Rochayati; Efita Elvandari; Treny Hera (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This study aimed to determine how the arrangement of the Kipas Chandani dance worked.  The problem was focused on the arrangement of the dance through the construction method I and construction method II.  To approach this problem, the theoretical reference from Jacqueline Smith 1985 in Ben Suharto's translation book entitled Dance Composition: A Practical Guide for Teachers was used.  The data were collected through the creative process of practical dance arrangement and recording of dance scripts all through the process of construction methods I and II and qualitatively been analyzed.  This study concluded that the arrangement of the Chandani Fan dance worked as a new creation dance material at the University of PGRI Palembang through the construction method I and construction method II with the result that the concept contained in the Chandani Fan dance was A visualization of today’s woman figure with all their life activities.  The display was packaged in the form of masculine and feminine movements.  In certain parts the movement pattern was made wider in order to create a masculine impression, while for the feminine movement pattern is manifested in soft, light, continuous and regular movements.